Clinical Manifestations, TSH and FT4 Levels During Initiation and Maintenance Therapy in Patients with Graves’ Disease at Dr. M. Djamil General Hospital, Padang, 2017–2022 - Rahmat, Nia Aulia; Dinda Aprilia; Dian Pertiwi; Rudy Afriant; Elfira Yusri; Yustini Alioes (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Graves’ disease is an autoimmune cause of hyperthyroidism marked by characteristic symptoms and abnormalities in TSH and FT4 levels. Management consists of an initial treatment phase followed by long-term maintenance, and variability in immune responsiveness may influence therapeutic outcomes. This study aimed to describe clinical manifestations and thyroid hormone profiles during initial and maintenance therapy among patients treated at Dr. M. Djamil General Hospital, Padang, from 2017 to 2022. Method: A descriptive cross-sectional design with total sampling was applied. Forty patients diagnosed with Graves’ disease were included. Clinical and laboratory variables were extracted from medical records, and univariate analysis was performed using SPSS v26. Results: The majority of patients were women aged 40–60 years. Palpitations were the most frequent symptom in both treatment phases, followed by excessive sweating, tremor, and exophthalmos. Treatment duration exceeded 24 months for the majority. Mean TSH increased from 0.11±0.17 µIU/mL in the initial phase to 0.62±1.03 µIU/mL during maintenance, while mean FT4 decreased from 47.09±32.79 pmol/L to 21.73±13.10 pmol/L. Discussion: The observed rise in TSH and decline in FT4 indicate biochemical improvement consistent with antithyroid drug responsiveness. The reduction in symptom frequency parallels hormonal stabilization, supporting the clinical utility of long-term therapy. The extended duration of treatment aligns with standard recommendations that emphasize sustained disease control to minimize the risk of relapse. Conclusion: Transition from initial to maintenance therapy was associated with symptomatic improvement and progressive normalization of thyroid function, emphasizing the importance of prolonged and well-supervised treatment in Graves’ disease.